3(2x+5)=53

Simple and best practice solution for 3(2x+5)=53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+5)=53 equation:


Simplifying
3(2x + 5) = 53

Reorder the terms:
3(5 + 2x) = 53
(5 * 3 + 2x * 3) = 53
(15 + 6x) = 53

Solving
15 + 6x = 53

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 6x = 53 + -15

Combine like terms: 15 + -15 = 0
0 + 6x = 53 + -15
6x = 53 + -15

Combine like terms: 53 + -15 = 38
6x = 38

Divide each side by '6'.
x = 6.333333333

Simplifying
x = 6.333333333

See similar equations:

| Y=-16x^2+5t+14 | | 1/2y=1/4 | | 1x+9-2x=-6 | | 8/0.62 | | -7(4f-6)=0 | | 4(5x+7)(2x+3)= | | 3q^2-80q+220=0 | | 4n^2+35n+43=-4n-5n^2+3 | | -3x+5y=-32 | | 5x+6x-72=90-7x | | (1/2x^6)(x^32y^8) | | 12=2(5x+4) | | y-10=-20x-10 | | k/3=14 | | 53=6*q | | 3(4x-10)=2x+7 | | 16x^2-8x-8= | | 4x+9x-84=63-8x | | 75+3y= | | Y=10x-1-3 | | 5.5+(7.9y)=y+11.4 | | 3-2(6-4x)=2+3(3x-6)-5 | | −z/4=−34 | | 10a-2b=-18 | | 535+4.5=12 | | 5.5+7.9x=11.4+x | | x^6+2x^3-x+1=0 | | 1,296/180 | | 3k^2+k=3k | | (7x+31)= | | 64x^2-48xy+9y^2=0 | | -9x+5y=52 |

Equations solver categories